Aware and tuned to care: Children with better distress recognition and higher sympathy anticipate more guilt after harming others. (11th September 2019) - Colasante, Tyler; Gao, Xiaoqing; Malti, Tina
Abstract : Helping children recognize the distress of their victims and feel sympathy may facilitate the optimal socialization of ethical guilt. With a sample of 150 eight‐year‐olds, we tested the main and interactive relations of distress recognition and sympathy to ethical guilt after hypothetically stealing and pushing. Better fear recognition and higher sympathy were uniquely associated with higher ethical guilt. The link between fear recognition and ethical guilt was stronger in children with higher sympathy. Beyond their unique contributions, distress recognition and sympathy may work in concert to facilitate ethical guilt after harming others. Statement of contribution What is already known on this subject Children are thought to express more guilt if they recognize their victims' distress and feel sympathy for them. However, there is little evidence for the direct roles of distress recognition and sympathy in children's guilt, and none for their joint contribution. What the present study adds The link between fear recognition and guilt was stronger in children with higher sympathy. Sympathy may help children harness and translate the awareness afforded by distress recognition into feelings of accountability and regret. This study was the first to clarify the main and additive roles of sympathy and distress recognition in children's anticipation of guilt after harming others. Promoting distress recognition and sympathy may represent a viable two‐step approach to inducing guilt in children after they violate others' welfare.